Entre communication politique et propagande : les publicités électorales de 1979 à 2005 - Karine Rivière-De Franco (Revue LISA)
Advertising and propaganda share a common purpose: to try to influence and modify people’s beliefs and behaviours though persuasion. This article intends to examine the advertisements produced by the Conservative Party and the Labour Party over seven electoral campaigns, highlighting the choices made by the parties in the making of this type of electoral communication (in terms of pictures, texts, slogans and logos), leading to a classification of those documents in different groups according to their content (positive, negative, both negative and personal, comparative), and showing how the messages are systematically repeated to make them easier to remember and to create a cumulative effect. These analyses will enable to determine to what extent the parties, the outgoing government and the official opposition, exert systematic actions over voters to make them adopt their ideas and vote for them.